Silver-Russell Syndrome: A Case Report - Hazan, Filiz; Apa, Hurşit; Demir, Korcan; Böber, Ece; Özkınay, Ferda (Fırat University, 2012)
Silver-Russell syndrome is an inherited disease that is characterized by intrauterine and postnatal growth retardation, relative macrocephaly, triangular face, body asymmetry and clinodactyly of the 5th finger, Hypomethylation of the imprinting control region that is localized in chromosomal region 11p15 is responsible for 35-65% of the cases. We present here a case that has phenotypic characteristics of Silver-Russell syndrome and growth hormone deficiency, and a definitive diagnosis made with determination of imprinting control region hypomethylation.

Silver-Russell sendromu, intrauterin ve postnatal büyüme geriliği, relatif makrosefali, üçgen yüz, vücut asimetrisi ve el 5. parmakta klinodaktili özelliklerinin görüldüğü bir genetik hastalıktır. Olguların %35-65'inden 11p15 kromozomal bölgesinde lokalize olan imprintlenme kontrol bölgesinin hipometilasyonu sorumludur. Burada, Silver Russell sendromu fenotipik özellikleri ve büyüme hormonu eksikliği bulunan, imprintlenme kontrol bölgesinin hipometilasyonu saptanması ile kesin tanısı konulan hasta sunulmuştur.
Silver-Russell Sendromu: Olgu Sunumu